Memes and their Meaning for the Study of Adult Learners: Civic Engagement in Chilean For-Profit Graduate Education - Lisa R. Brown; Lorilee R. Sandmann (Adult Education Research Conference, 2013)
The civic engagement commitment and mission among the growing number of forprofit higher education enterprises remains empirically unexplored. Spiral Dynamic Theory (SDT) is proposed as a theoretical framework to examine levels of civic engagement in complex contexts associated with private for-profit, graduate-level education.